2023
DOI: 10.1007/s40258-023-00806-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review of the Psychometric Performance of Generic Childhood Multi-attribute Utility Instruments

Abstract: Background Childhood multi-attribute utility instruments (MAUIs) can be used to measure health utilities in children (aged ≤ 18 years) for economic evaluation. Systematic review methods can generate a psychometric evidence base that informs their selection for application. Previous reviews focused on limited sets of MAUIs and psychometric properties, and only on evidence from studies that directly aimed to conduct psychometric assessments. Objective This study aimed to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 113 publications
2
16
0
Order By: Relevance
“…Economic evaluation is a cornerstone of health economics and is used to inform resource allocation decisions across technologies, such as medicines, services, and tests [ 1 , 2 ]. When considering interventions targeted at children and young people, the development of health-related quality of life (HRQoL) instruments specific to the measurement of child health [ 3 , 4 ], and the valuation of child HRQoL anchored on a 0–1 scale required for estimation of quality-adjusted life-years (QALYs) [ 5 ], are key elements. There is a lack of consensus, though, about fundamental aspects of these research methods used in valuing child HRQoL [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Economic evaluation is a cornerstone of health economics and is used to inform resource allocation decisions across technologies, such as medicines, services, and tests [ 1 , 2 ]. When considering interventions targeted at children and young people, the development of health-related quality of life (HRQoL) instruments specific to the measurement of child health [ 3 , 4 ], and the valuation of child HRQoL anchored on a 0–1 scale required for estimation of quality-adjusted life-years (QALYs) [ 5 ], are key elements. There is a lack of consensus, though, about fundamental aspects of these research methods used in valuing child HRQoL [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous characteristics that might affect and limit the comparability of evidence on HRQoL and QALYs in children and young people. However, in a recent systematic review of measurement and valuation of child HRQoL [ 3 ], a review of the psychometric performance of generic childhood multi-attribute utility instruments [ 4 ], and a review of the methods used to value child HRQoL [ 8 ], authors concluded that the reporting of such studies is often incomplete and inconsistent. Poor reporting of methods used to value child HRQoL and the values derived makes it difficult for users of these instruments to make informed choices and for decision makers to use the evidence in an informed way.…”
Section: Introductionmentioning
confidence: 99%
“…An instrument’s measurement accuracy can be informed by assessment of its psychometric properties. Although there is some evidence available regarding the individual psychometric performance of generic paediatric HRQoL instruments [ 9 ], there is a paucity of evidence on the comparative psychometric performance of these instruments (i.e., how these instruments perform compared with one another in the same sample) in terms of validity, reliability, and responsiveness [ 10 , 11 ]. There are challenges measuring HRQoL in children when compared with adults, which may be why such evidence is still lacking [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Unlike adults, children have a broad developmental range, precluding the use of a single approach for measuring HRQoL in all children [ 13 ]. There have been five previous reviews of generic paediatric HRQoL instruments [ 9 11 , 14 , 15 ]. A 2015 systematic review examined HRQoL instruments accompanied by preference weights that were previously used in paediatric populations: the Adolescent Health Utility Measure, Assessment of Quality of Life (AQoL-6D), Child Health Utility (CHU9D), the EuroQol Group’s EQ-5D-Y-3L, Health Utilities Index Mark 2 (HUI2) and Mark 3 (HUI3), 16D, 17D, and the Quality of Wellbeing Scale (QWB) [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The EQ-5D-Y-3L is one of the most cited generic preference-weighted HRQoL measures available for young children [ 44 ]. It has however not been used to measure HRQoL in children dependent on technology for breathing and requires psychometric validation.…”
Section: Introductionmentioning
confidence: 99%